Effects of Dust Exposure to Lung Function on Cement Loading Worker - Putra, Ezi Dwi; Raharjo, Mursid; Nurjazuli, Nurjazuli (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Exposure to environmental contaminants in the work area such as dust can cause disruption of lung function of workers. If lung function is disrupted, it certainly can reduce one's health condition which will have an impact on decreasing work productivity. This study aims to analyze the impact of dust exposure on lung function disorders in obese workers and who have smoking habits. This study uses a cross sectional design. The results showed there was a relationship between the level of inhaled dust and obstructive pulmonary function disorders in respondents who had smoking habits (p value = 0.013) and in respondents who had excess BMI (p value = 0.009).